111Indium autologous granulocytes in the detection of inflammatory bowel disease. Issue 9 (September 1985) - Saverymuttu, S H; Peters, A M; Crofton, M E; Rees, H; Lavender, J P; Hodgson, H J; Chadwick, V S
Abstract : Indium leucocyte scanning and measurement of faecal Indium leucocyte excretion are techniques which have recently been introduced for assessing patients with inflammatory bowel disease. The methodology has recently been made more specific for acute inflammation by labelling pure granulocytes rather than the mixed leucocyte preparation. To determine the accuracy of this modified technique in detecting inflammatory bowel disease, we have prospectively compared Indium granulocyte scanning and faecal In granulocyte excretion with rectal histology and contrast bowel radiology as screening procedures in 100 patients with suspected inflammatory bowel disease. Thirty three patients were shown to have inflammatory bowel disease - 24 with Crohn's disease and nine with ulcerative colitis or indeterminate colitis. Overall the respective sensitivities for detecting inflammatory bowel disease were 97% for faecal Indium granulocyte excretion, 94% for Indium granulocyte scanning, 79% for radiology and 70% for rectal histology. The superiority of In granulocytes over radiology and rectal histology in detecting inflammatory bowel disease was, in the main, due to the difficulty in diagnosing Crohn's with conventional techniques. Although three of the patients with ulcerative colitis and indeterminate colitis had normal sigmoidoscopic appearances - all had abnormal rectal histology. No patient with a non-inflammatory bowel disorder had a positive In granulocyte scan or a raised faecal excretion. These results show that investigations using In granulocytes are accurate in identifying inflammatory bowel disease and offer important advantages over conventional procedures for detecting Crohn's disease.